MINIINVASIVE APPROACH TO THE TREATMENT OF LIVER CYSTS - Vyhnanek, Jaroslav; Duda, Miloslav; Gryga, Adolf; Dlouhy, Michael; Czudek, Stanislav (Biomedical papers, 1999)
During the period from 1995 to 1997 we followed and treated six patients for liver cysts. Diagnostics was basednot only on clinical examination but also on ultrasonography and computational tomography (CT). Surgery isapplied in solving larger cysts damaging liver parenchyma and causing pressure symptomatology. Nowadays mostcysts can be solved by means of laparoscopy.
Keywords: Liver cysts / Laparoscopy